Decreased Cognitive Function in Danish Children with Epilepsy - Bogut, Laura; Andersen, Kaja; Grejsen, Judy; Gimenez-Rico, Maria Jose Miranda; Debes, Nanette Monique Mol (Neuropediatrics, 2023)
Objective Children with epilepsy have a significantly increased risk of cognitive impairment. EpiTrack Junior is a screening tool developed for fast assessment of cognitive function in children with epilepsy. The tool is validated for German children. This cohort study aims to investigate the differences in cognitive function between healthy Danish children and Danish children diagnosed with epilepsyMethods The cognitive function of 204 healthy controls and 90 children and adolescents diagnosed with epilepsy was examined using EpiTrack Junior. The participants of the control group were aged 6 to 16 years. The patients were aged 6 to 20 years. Statistical analyses were performed with the use of SPSS Statistics.Results The control group showed significantly higher scores than the patient group in three of six subtests and total test scores (p-values ranging from 0.033 to <0.001). When grouped according to the EpiTrack Junior guidelines, more patients showed scores “below average” or “poor” compared to the control group. The age-corrected total score was not associated with antiepileptic drug treatment (p-value of 0.732) nor with a history of focal seizures (p-value of 0.215). A history of generalized tonic–clonic seizures (GTCS) was associated with a higher EpiTrack Junior score (p-value of 0.035).Conclusion The patient group showed statistically significant lower test scores compared to the control group confirming the relationship between impaired cognitive function and childhood epilepsy. Furthermore, a correlation between a higher EpiTrack Junior score and the presence of GTCS was found. Focal seizures and antiepileptic drug treatment were not associated with the EpiTrack Junior score.
Keywords: cognitive function; EpiTrack Junior; attention; executive functions; childhood epilepsy